Kyrgyz Republic Economic Update, Winter 2016 : A Resilient Economy on a Slow Growth Trajectory - World Bank Group (World Bank, Washington, DC, 2017)
The first part of the Economic Update analyzes recent macroeconomic trends and presents an assessment of the country’s short- and medium-term outlook. The Kyrgyz economy has remained resilient to the adverse regional environment, but growth prospects are modest and adjustments needed.Overall, the macroeconomic situation improved slightly since the shock stemming from Russia’s recession hit in [late 2014]. In the medium term, growth prospects should improve as remittances and the external demand environment recover.However, although risks have moderated, they remain elevated. The main sources of risk relate to possible adverse developments in neighboring economies, principally related to oil prices and exchange rate dynamics. This implies the need to rebuild fiscal buffers over the next 2-3 years through a mix of expenditure consolidation and revenue mobilization. The Special Focus Section discusses tax revenue reforms, presenting the findings of a recent World Bank Tax Administration Diagnostics Assessment (TADAT).